An Analysis Of D-Band Gunn Diode For Millimeter Wave Application - Masuaud, Zaffrul Zulkarnain Aziz; Othman, Mohd Azlishah; Ali, Nadhirah; Sulaiman, Hamzah Asyrani; Abd Aziz, Mohamad Zoinol Abidin (Asian Research Publishing Network (ARPN), 2015)
-